A Field-Based Evaluation of the Reliability of Empirical Formulae for Quantifying the Longitudinal Dispersion Coefficient in Small Channels - Marianni A. Nogare; Bernard O. Bauer (Geosciences, 2022)
The majority of formulae for predicting in-channel mixing by longitudinal dispersion are based on empirical evidence from medium to large rivers, whereas small creeks and streams are under-represented despite their hydrological and ecological importance. In this study, twenty-six formulae for predicting the longitudinal dispersion coefficient (Kx) were evaluated for their applicability to small channels using field measurements and hydraulic modeling. Predicted values for Kx, following guidelines recommended in the original publications for the formulae, were compared to measured dispersion coefficients obtained from sodium-chloride plumes injected into two small channels (a concrete-lined, trapezoidal channel and a small, natural stream) based on fitting the Hayami solution to the one-dimensional advection-dispersion equation (ADE) to each plume. The predicted Kx coefficients from the formulae were also utilized to create model-simulated plumes, which were compared to those measured well downstream of the point of injection. The findings demonstrate that the predictive accuracy of the twenty-six formulae was extremely variable; none were able to predict the dispersion process in the small channels with better than ± 50% accuracy. These results show that “universal” formulae are plagued with a large degree of uncertainty and should be used with caution when applied to small channels, although more robust predictions are possible with some formulae if site-specific data are available for calibration.